DEVELOPING TEACHING MEDIA POWTOON FOR WRITING DESCRIPTIVE TEXT AT GRADE 8 STUDENTS OF SMPN 6 PERCUT SEI TUAN - Dio Ilham Prasetyo Siregar; Rika (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The objective of this study is to develop PowToon as media for teaching the 8 students in writing descriptive text at SMPN 6 Percut Sei Tuan. This study used the qualitative descriptive method. This research was conducted based on educational research and development (R&D) through six steps, namely: gathering data, analyzing data, designing media, validating by the expert, revising media, and final product. The Instrument of Collecting Data was questionnaire. The finding showed that one video of PowToon was used to teach English writing to Junior High School. The developed media PowToon had been validated by two experts and the average score has gotten was 87%. It was categorized “Excellent” since that the developed to teaching media PowToon for writing skills were suitable for the 8 grade students of SMPN 6 Percut Sei Tuan.